Kajian Yuridis Hak Angket Dewan Perwakilan Rakyat Terhadap Komisi Pemberantasan Korupsi (Dikaji dari Perspektif Hukum Tata Negara) - Adityanatha, I Gusti Ngurah (Acta Comitas : Jurnal Hukum Kenotariatan, 2019)
The House of Representatives as a legislative commission has the privilege of being a right of inquiry in order to run a system of government that is check and balances. With regard to the right of inquiry The House of Representatives to The Corruption Eradication Commission, it is feared to be used as a means to influence and interfere with The Corruption Eradication Commission, even weaken the role of The Corruption Eradication Commission as an independent institution free from any influence of power. Regarding the formulation of the problem in this scientific research is, how the position of The Corruption Eradication Commission in the constitutional system in Indonesia as an independent institution? and whether The House of Representatives may use the right of inquiry to The Corruption Eradication Commission? The type of research used in this scientific research is normative legal research. The Corruption Eradication Commission is an independent state commission in Indonesia that is outside the realm of the three original powers of executive, legislative, and judicial (trias potilica) in the state administration system in Indonesia, so that The Corruption Eradication Commission can not be subject to the right of inquiry by The House of Representatives. It is also reinforced by the subject of a limited questionnaire on the implementation of a law and / or government policy carried out solely by The President, Vice President, State Minister, Commander of the Indonesian National Army, the Chief of the Indonesian National Police, the Attorney General, or the non-ministerial government agencies. Dewan Perwakilan Rakyat sebagai lembaga legislatif memiliki hak istimewa yakni hak angket dalam rangka menjalankan sistem pemerintahan yang bersifat check and balances. Terkait dengan hak angket terhadap Komisi Pemberantasan Korupsi oleh Dewan Perwakilan Rakyat, dikhawatirkan digunakan sebagai sarana untuk mempengaruhi dan mengintervensi Komisi Pemberantasan Korupsi, bahkan dapat melemahkan peran Komisi Pemberantasan Korupsi sebagai lembaga independen dan bebas dari pengaruh kekuasaan manapun. Mengenai rumusan masalah dalam karya ilmiah ini yaitu, bagaimanakah kedudukan Komisi Pemberantasan Korupsi dalam sistem ketatanegaraan di Indonesia sebagai lembaga independen? dan apakah Dewan Perwakilan Rakyat dapat menggunakan hak angket terhadap Komisi Pemberantasan Korupsi? Jenis penelitian yang digunakan pada karya ilmiah ini adalah penelitian hukum normatif. Komisi Pemberantasan Korupsi merupakan komisi negara independen di Indonesia yang berada di luar ranah tiga poros kekuasaan asli yaitu eksekutif, legislatif, dan yudisial (trias potilica) dalam sistem ketatanegaraan di Indonesia, sehingga Komisi Pemberantasan Korupsi tidak dapat dijadikan subjek dari hak angket oleh Dewan Perwakilan Rakyat. Hal tersebut juga diperkuat dengan subjek dari hak angket yang terbatas pada pelaksanaan suatu undang-undang dan/atau kebijakan pemerintah yang dilaksanakan sendiri oleh Presiden, Wakil Presiden, Menteri Negara, Panglima Tentara Nasional Indonesia, Kepala Kepolisian Negara Republik Indonesia, Jaksa Agung, atau pimpinan lembaga pemerintah non-kementerian.